From pixel to voxel: a deeper view of biological tissue by 3D mass spectral imaging. (February 2011) - Ye, Hui; Greer, Tyler; Li, Lingjun
Three dimensional mass spectral imaging (3D MSI) is an exciting field that grants the ability to study a broad mass range of molecular species ranging from small molecules to large proteins by creating lateral and vertical distribution maps of select compounds. Although the general premise behind 3D MSI is simple, factors such as choice of ionization method, sample handling, software considerations and many others must be taken into account for the successful design of a 3D MSI experiment. This review provides a brief overview of ionization methods, sample preparation, software types and technological advancements driving 3D MSI research of a wide range of low- to high-mass analytes. Future perspectives in this field are also provided to conclude that the outlook for 3D MSI is positive and promises ever-growing applications in the biomedical field with continuous developments of this powerful analytical tool.